2016
DOI: 10.1016/j.lungcan.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age and comorbidity on treatment of non-small cell lung cancer recurrence following complete resection: A nationally representative cohort study

Abstract: Objective-Older patients with non-small cell lung cancer (NSCLC) are less likely to receive guideline-recommended treatment at diagnosis, independent of comorbidity. However, national data on treatment of postoperative recurrence are limited. We evaluated the associations between age, comorbidity, and other patient factors and treatment of postoperative NSCLC recurrence in a national cohort.Materials and Methods-We randomly selected 9,001 patients with surgically resected stage I-III NSCLC in 2006-2007 from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 41 publications
5
42
0
Order By: Relevance
“…The age disparity that remains even after correcting for comorbidity level, however, does raise the question of whether older patients have lower access to genetic testing not because they are sicker, but simply because they are older. Comorbidity-independent age-based disparity has already been documented in the more general context of active treatment for NSCLC (42)(43)(44), and our result implies that this disparity may also exist in targeted therapy treatment specifically. Further investigation is warranted to determine whether this disparity could be due to patient preferences or to inappropriate undertreatment.…”
Section: Discussionsupporting
confidence: 70%
“…The age disparity that remains even after correcting for comorbidity level, however, does raise the question of whether older patients have lower access to genetic testing not because they are sicker, but simply because they are older. Comorbidity-independent age-based disparity has already been documented in the more general context of active treatment for NSCLC (42)(43)(44), and our result implies that this disparity may also exist in targeted therapy treatment specifically. Further investigation is warranted to determine whether this disparity could be due to patient preferences or to inappropriate undertreatment.…”
Section: Discussionsupporting
confidence: 70%
“…Otherwise, in a study of early NSCLC, Masaki et al [23] reported that patients with early-stage peripheral NSCLC were more likely to have distant failure. In a study by Melisa et al [24], their data indicated that the recurrence rate of distant sites was higher than that at local sites in younger patients with NSCLC and peripheral NSCLC. Although the populations were different between our cohort and the above two studies, we obtained similar predictors for the first failure pattern for NSCLC patients.…”
Section: Discussionmentioning
confidence: 96%
“…Cancer patients with comorbid conditions are generally less likely to receive surgery or other curative treatment. The increased risk of treatment toxicity, side effects and post-operative complications associated with comorbidity or the concern that the life expectancy of patients with comorbidity is insufficient to justify the use of potentially toxic therapy may prevent clinicians from aggressive treatment choices [30]. Additionally, there was a lack of high-level evidence on the effect of cancer therapies among patients with comorbidity since most of randomized controlled trials always exclude those with concomitant conditions.…”
Section: Discussionmentioning
confidence: 99%